Implications of a Psychological Approach to Collective Remembering: Social Representations as Cultural Ground for Interpreting Survey and Experimental Results. (April 2021) - Liu, James H.; Khan, Sammyh S.
Psychology has become connected to the "memory boom" in research, that highlights the concept of social representations, defined as a shared system of knowledge and belief that facilitates communication about social objects where culture is conceptualized as a meta-system of social representations mediated by language, symbols, and their institutional carriers. Six articles on collective remembering, including survey results, text analysis, and experiments, are summarized in this introduction. All rely on content-rich meanings, embedded in sociocultural contexts that influence the results of the surveys and experiments. In the cases of Germany and China, the "historical charter" of the states in the late 19th century was ruptured, resulting in substantially different expressions of nationalism and national identity (in Germany) and filial piety and nationalism (in China) today. Surveys on the organization of living historical memory in Hungary and Finland found that the European Union formed an enduring social context for the formation of memory groups regarding recent history. Finally, in experiments, historical reminders are likely to be anchored in existing networks of meaning, and prime people about what they already believe, rather than exert independent causal effects. This anchoring of historical memory in communicating societies explains why the experimental results in this area are so inconsistent.